Building the new international science of the agriculture–food–water–environment Nexus in China and the world. Issue 11 (1st December 2016) - Zhu, Xinguang; Parry, Martin; Lu, Yonglong; Heard, Matthew; Ying, Guangguo; Vaughan, Simon; Shen, Jianbo; Jenkins, Alan; Wang, Yunpeng; Lacorte, Silvia; Ouyang, Tingping; Salcedo, Francisco Pedrero; et al.
Abstract: The multiple, complex and systemic problems of the agriculture–food–water–environment nexus ("Nexus") are among the most significant challenges of the 21st century. China is a key site for Nexus research amidst profound socio‐environmental problems. The policy implications of these problems have been authoritatively summarized elsewhere. This study presents discussions at an international workshop in Guangzhou that asked instead "What science is needed to deliver the growing policy commitments regarding these challenges? And, What changes are needed to the science itself?" Understanding and effective intervention regarding the Nexus calls for a paradigm shift: to a new kind of science of (capacity for) international, interdisciplinary, and impactful research working with and within complex socio‐natural systems. We here argue that science must become proactive in approach, striving only for "minimal harm" not "silver bullet" solutions, and adopting an explicitly long‐term strategic perspective. Together, these arguments lead to calls for reorienting science and science policy in three ways: from short‐term remediation to longer‐term optimization; from a focus on environmental threats to one on the opportunities for international collaborative learning; and toward supporting new forms of scientific career. We bring these points together by recommending a new form of scientific institution: a global network of collaborative Nexus Centres, under the umbrella of a global Food Nexus Organization akin to those of the human genome and proteome.